FUNDRAISING SERTA PENDISTRIBUSIAN PAJAK DAN ZAKAT DI INDONESIA - Eny Latifah; Donny Prastya; Suroso Suroso (JISEF : Journal Of International Sharia Economics And Financial, 2022)
The purpose of this study is to determine the role of zakat in the economic sphere, especially in fundraising and distribution. The research method used is library research by combining data sources from books and reports on previous research results. The result of this research is that tax fundraising can be seen from the performance of tax officers in carrying out their duties in ensuring that taxpayers fulfill their tax obligations while fundraising zakat comes from 5 groups of obligatory zakat whether issued for zakat fitrah or zakat maal. We can know the distribution of taxes from the taxes collected from the income received by each taxpayer, which will be used and managed by the government for the development of areas in need, while the distribution of zakat through institutions such as BAZNAS, LAZ, LAZISMU, LAZINU and others to be given to mustahik zakat taking into account the provisions of Islamic sharia both from the terms and pillars that exist.